Taking state of biodiversity reporting into the information age – A South African perspective - Poole, Carol Jean; Skowno, Andrew Luke; Currie, Jock C.; Sink, Kerry Jennifer; Daly, Brenda; von Staden, Lize (Frontiers in Ecology and Evolution, 2023)
South Africa’s National Biodiversity Assessment (NBA) is the primary tool for monitoring and reporting on the state of biodiversity, with a focus on spatial information and key indicators. The NBA distills information that informs policies and strategies, meets national and international reporting requirements, and helps prioritize limited resources for managing and conserving biodiversity. The three previous versions of the NBA (2004, 2011 and 2018) are in the form of detailed thematic technical reports and a synthesis report, served on a simple, static web page. Selected spatial products from the report are available via a dedicated web platform (http://nba.sanbi.org.za/). While all methods and data are clearly described in the technical reports, most of the underlying analyses are inaccessible, lacking reproducibility and transparency. This makes iterative updates to indicators or metrics challenging and inefficient, complicates version control, and exacerbates the risk of capacity, knowledge and data loss during staff turnover. To move the assessment process into the information age we aim to develop well documented and reproducible workflows, and to serve the indicators and their accompanying synthesis on an interactive web platform that facilitates uptake. Achieving these aims will deliver efficiency, greater transparency and trust in future NBA products and will strengthen communication and engagement with the content by the many different users of those products. While these visions will not be realized overnight, the skills and systems required to achieve them can be adaptively built towards an improved NBA that better serves the needs of our society.